Financial Management Strategies of Village Enterprises in Kotabaru - Aliyudin, Aceng; Erliany Syaodih; Veranita, Mira (International Journal Administration, Business & Organization, 2026)
This study aims to analyze the implementation, approach, and strategy of productivity-based financial management of Village-Owned Enterprises (BUMDes) in Kotabaru District, Karawang Regency. This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving BUMDes management and relevant stakeholders. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the implementation of BUMDes financial management has been carried out through sequential stages, namely financial planning, fund utilization, financial recording, financial reporting, as well as accountability and evaluation. The productivity-based financial management approach is oriented toward the effective use of financial resources to support productive and sustainable village business activities. Meanwhile, the financial management strategy to enhance business productivity is implemented through strengthening business-oriented budgeting, improving financial administration, and reinforcing policy support from the village government along with the commitment of BUMDes management. Based on these findings, it can be concluded that the financial management of BUMDes in Kotabaru District, Karawang Regency has been administratively implemented and oriented toward productivity. However, further improvement in human resource capacity and continuous assistance is still required to optimize the performance and sustainability of BUMDes business activities.